Modeling and Simulation of the Interstitial Medium Deformation Induced by the Needle Manipulation During Acupuncture (Communications in Computational Physics, 2020)
In this paper, we study the effects of inserted needle on the subcutaneousinterstitial flow. A goal is to describe the physical stress affecting cells during acupuncturetreatment. The model consists of the convective Brinkman equations to describethe flow through a fibrous medium. Numerical studies in FreeFem++ are performedto illustrate the acute physical stress developed by the implantation of a needle thattriggers the physiological reactions of acupuncture. We emphasize the importance ofnumerical experiments for advancing in modeling in acupuncture.